2017
DOI: 10.1186/s12870-017-1181-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the GRMZM2G174449 promoter to identify Rhizoctonia solani-inducible cis-elements in maize

Abstract: BackgroundBanded leaf and sheath blight (BLSB), caused by the necrotrophic fungus Rhizoctonia solani, is a highly devastating disease in most maize and rice growing areas of the world. However, the molecular mechanisms of perceiving pathogen signals are poorly understood in hosts.ResultsHere, we identified a Rhizoctonia solani-inducible promoter pGRMZM2G174449 in maize. Deletion analysis showed that the −574 to −455 fragment was necessary for pGRMZM2G174449 in responding to R. solani and this fragment containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The tissue-specific expression of transgenes plays a critical role in biotechnology crops because it avoids fitness costs caused by constitutive expression of target genes [ 9 ]. However, the information about the core cis-acting elements controlling tissue-specific expression is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue-specific expression of transgenes plays a critical role in biotechnology crops because it avoids fitness costs caused by constitutive expression of target genes [ 9 ]. However, the information about the core cis-acting elements controlling tissue-specific expression is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, inducible promoters greatly increase the transcription level of genes under specific physical or chemical signals [ 5 ], this is different from constitutive promoters. At present, a great number of inducible promoters have been isolated, including light-inducible, heat-inducible and trauma-inducible [ 6 , 7 , 8 , 9 , 10 ]. Abiotic stress is a major obstacle for crop production, and the promoters of many genes related to abiotic stress have been cloned and applied in crop biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…A promoter is a DNA sequence containing a variety of specific regulatory elements that regulates gene expression 20, 21 . To date, studies in plants have focused on constitutive promoters (with no spatiotemporal or tissue‐specific expression patterns), 22‐26 tissue‐specific promoters (with tissue‐specific expression patterns), 27‐30 and pathogen‐inducible promoters (with disease stress‐induced expression patterns) 31‐33 . Compared with the above promotor types, knowledge of insect‐inducible promoters lags far behind, and to date, only a very few insect‐inducible promoters have been reported 34‐37 …”
Section: Introductionmentioning
confidence: 99%
“…A previous study identified that the promoter of the R. solani-induced genes commonly harbors four types of cis-element sequences (GCTGA, TATAT, GTTGA, and TATTT) (33,34). To test whether the upregulated genes also carry the cis-element motifs, the 1.5 kb of promoter sequences from 31…”
Section: Identification Of Rhizoctonia Solani Responsive Cis-elementsmentioning
confidence: 99%